A ANALISIS EFEKTIVITAS PENGGUNAAN APLIKASI ZOOM PADA PROSES PEMBELAJARAN DARING DI MASA PANDEMI COVID-19: Efektivitas Aplikasi Zoom Pada Proses Pembelajaran Daring - Hapsari Ayuning Lestari; Meidawati Suswandari (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
ABSTRACTThis research was conducted with the aim of knowing the effectiveness of using the zoom application in learning at school. This writing was done by literature study. The object of this research is the use of the zoom application in the learning process. The research subjects were students in the upper grades of elementary school. The method used in this research is the literature study method. The data collection technique in this research is looking for journals contained in electronic media such as the internet, Google Scholar and Google Scholar. The results of the study indicate that the use of the zoom application is effectively used in the learning process during the pandemic. Barrier distance so that face-to-face learning cannot be done. Keywords: Effectiveness, Zoom Application, Learning Process